Adaptive attributes of tropical forage species to acid soils. V. Differences in phosphorus acquisition from less available inorganic and organic sources of phosphate - Rao, Idupulapati M.; Borrero, V.; Ricaurte Oyola, José Jaumer; García, Ramiro (Informa UK Limited, 1999)
Low phosphorus (P) supply is a major limitation to pasture establishment and production in highly weathered acid soils. Previous research showed that the forage legume, Arachis pintoi, was more efficient in acquiring P from infertile acid soils than the forage grass, Brachiaria dictyoneura. The main objective of the present study was to determine whether the higher P‐uptake efficiency (defined as “milligrams of P uptake in shoot biomass per unit root length") of the legume results from its greater ability to mobilize P from less available forms of phosphate (aluminum phosphate and organic P). The grass, Brachiaria dictyoneura CIAT 6133, and the legume, Arachis pintoi CIAT 17434, were grown in the greenhouse for 75 days in monoculture or in association. They were planted in large plastic containers holding either one of two acid soils of contrasting texture (sandy or clay loam) and amended with different sources of P. Four sources of P were used: di‐calcium phosphate (Ca‐P), aluminum phosphate (Al‐P), phytic acid (organic‐P), and cow manure (dung‐P). Except for Al‐P, which was applied at two levels (20 and 100 kg P ha−1), the other sources were applied at 20 kg P ha−1. We found greater differences in P acquisition between the grass and legume than between the two types of acid soil. Acquisition of P by the legume was markedly greater than that of the grass, regardless of the source of P. The legume accessed 205 to 220% more sparingly soluble, inorganic P from soil compared to the grass. The relationship between shoot P uptake and root length showed that the legume roots acquired more P per unit root length than did the grass roots. The superior ability of the legume roots to acquire P from different P sources was associated with higher levels of inorganic P in roots. These results indicate that one reason for the success of Arachis pintoi in competing with aggressive grasses was its ability to acquire P from less available forms present in acid soils. This study also suggests that the measurement of inorganic‐P levels in roots may serve as a selection method to evaluate tropical forage legumes for their adaptation to less available P sources in P‐deficient acid soils.